(untitled) (Research, Society and Development, 2024)
Objective: Search for articles, books and other studies on flower therapy from its functioning, origin and benefits in dentistry. Methodology: Searches were made for online materials, aiming to obtain information, studies, articles and other research through the following databases: The Cochrane Library, Web of Science, Research, society and development journal, DeCs, Science Direct, VHL /BIREME, PUBMED Central, Scielo and Google Academy. Results: Our search resulted in 37 articles. Conclusion: Floral Therapy, in addition to being used in various health settings, has benefits in post and pre dental care, such as its function against fear and anxiety.